In vitro activity of anti-malarial ozonides against an artemisinin-resistant isolate. (December 2017) - Baumgärtner, Fabian; Jourdan, Joëlle; Scheurer, Christian; Blasco, Benjamin; Campo, Brice; Mäser, Pascal; Wittlin, Sergio
Abstract Background Recently published data suggest that artemisinin derivatives and synthetic peroxides, such as the ozonides OZ277 and OZ439, have a similar mode of action. Here the cross-resistance of OZ277 and OZ439 and four additional next-generation ozonides was probed against the artemisinin-resistant clinical isolatePlasmodium falciparum Cam3.I, which carries the K13-propeller mutation R539T (Cam3.IR539T ). Methods The previously described in vitro ring-stage survival assay (RSA0–3h ) was employed and a simplified variation of the original protocol was developed. Results At the pharmacologically relevant concentration of 700 nM, all six ozonides were highly effective against the dihydroartemisinin-resistantP. falciparum Cam3.IR539T parasites, showing a per cent survival ranging from <0.01 to 1.83%. A simplified version of the original RSA0–3h method was developed and gave similar results, thus providing a practical drug discovery tool for further optimization of next-generation anti-malarial peroxides. Conclusion The absence of in vitro cross-resistance against the artemisinin-resistant clinical isolate Cam3.IR539T suggests that ozonides could be effective against artemisinin-resistantP. falciparum. How this will translate to the human situation in clinical settings remains to be investigated.